The BiZiFED project: Biofortified zinc flour to eliminate deficiency in Pakistan. Issue 1 (17th January 2019) - Ohly, H.; Broadley, M. R.; Joy, E. J. M.; Khan, M. J.; McArdle, H.; Zaman, M.; Zia, M.; Lowe, N.
Abstract: Zinc deficiency is a global public health problem, affecting ~17% of the world's population, with the greatest burden in low‐ and middle‐income countries. An increasing body of evidence suggests that biofortification may be a cost‐effective and sustainable approach to reducing zinc and other micronutrient deficiencies. Biofortification enhances the nutritional quality of food crops through conventional plant breeding techniques and agronomic practices. This paper presents ongoing research on biofortification in Pakistan, where over 40% of women are zinc deficient. The Biofortified Zinc Flour to Eliminate Deficiency ( BiZiFED ) project aims to investigate the impact of biofortification as a strategy to alleviate zinc deficiency in Pakistan. The project is supported by the Biotechnology and Biological Sciences Research Council (BBSRC) Global Challenges Research Fund from May 2017 to April 2019. This paper outlines the four objectives and work packages within the BiZiFED project: (1) a double‐blind, randomised controlled trial to examine the effect of consuming flour made from a high zinc variety of biofortified wheat (Zincol‐2016/NR‐421) on dietary zinc intake and status; (2) a cost‐effectiveness study to assess the health and economic impact of agronomic biofortification of wheat; (3) a mixed methods study to explore the cultural acceptability and sustainability of biofortification in Pakistan; (4) capacity building and development of long‐term research partnerships in Pakistan. The findings will contribute to the evidence base for the potential impact of biofortification to alleviate zinc deficiency among the poorest communities.